Influence of Mpv17 on Hair-Cell Mitochondrial Homeostasis, Synapse Integrity, and Vulnerability to Damage in the Zebrafish Lateral Line - Holmgren, Melanie; Sheets, Lavinia (Frontiers in Cellular Neuroscience, 2021)
Noise exposure is particularly stressful to hair-cell mitochondria, which must produce enough energy to meet high metabolic demands as well as regulate local intracellular Ca2+ concentrations. Mitochondrial Inner Membrane Protein 17 (Mpv17) functions as a non-selective channel and plays a role in maintaining mitochondrial homeostasis. In zebrafish, hair cells in mpv17a9/a9 mutants displayed elevated levels of reactive oxygen species (ROS), elevated mitochondrial calcium, hyperpolarized transmembrane potential, and greater vulnerability to neomycin, indicating impaired mitochondrial function. Using a strong water current to overstimulate hair cells in the zebrafish lateral line, we observed mpv17a9/a9 mutant hair cells were more vulnerable to morphological disruption and hair-cell loss than wild type siblings simultaneously exposed to the same stimulus. To determine the role of mitochondrial homeostasis on hair-cell synapse integrity, we surveyed synapse number in mpv17a9/a9 mutants and wild type siblings as well as the sizes of presynaptic dense bodies (ribbons) and postsynaptic densities immediately following stimulus exposure. We observed mechanically injured mpv17a9/a9 neuromasts, while they lost a greater number of hair cells, lost a similar number of synapses per hair cell relative to wild type. Additionally, we quantified the size of hair cell pre- and postsynaptic structures and observed significantly enlarged wild type postsynaptic densities, yet relatively little change in the size of mpv17a9/a9 postsynaptic densities following stimulation. These results suggest impaired hair-cell mitochondrial activity influences synaptic morphology and hair-cell survival but does not exacerbate synapse loss following mechanical injury.